TEACHING CAREGIVERS TO ACTIVELY ENGAGE OLDER ADULTS IN DAILY ACTIVITIES: CAREGIVERS' PERFORMANCE AND PERSPECTIVES. (11th November 2018) - Kempen, G I J M; Metzelthin, S F
Abstract: Our aging society asks for sustainable long-term care services for older adults. Previous research has shown that active engagement in daily activities contributes to successful aging. However, with increasing age older adults are often in need for outpatient or inpatient services due to functional limitations. In the best case, caregivers adapt their level of assistance to the capabilities of older adults and stimulate older adults to do as much as possible by themselves. However, in practice caregivers often tend to take over tasks, which unintentionally can result in further functional decline. During the last decade, several approaches (e.g., Reablement or Function Focused Care) have been developed and implemented to change the philosophy of care across all levels from doing things for towards doing things with older adults. During this symposium, five presenters from three different countries talk about different approaches to teach caregivers to actively engage older adults in daily activities. The focus of the presentations are on caregivers' performance and perspectives. The first presentation is about the experiences of home care staff with the 'Stay Active at Home' program. The second presenter speaks about the effects of Reablement on caregivers' working conditions and job satisfaction. The next presentation is about the implementation of Function Focused Care in assisted living facilities. The fourth presenter talks about the impact of the DAIly NURSE intervention on the behavior of nursing home staff. Finally, the last presentation is about teaching nursing home staff to provide more function and behavior focused care.